As compras públicas sustentáveis no Brasil: um estudo nas universidades federais - Hegenberg, Juliana Trianoski (2013)
The goal of this study is to analyze the implementation of Sustainable Public Procurement in the Brazilian federal universities. The research is applied as its purpose and exploratory and descriptive as to their overall goals. The approach is both qualitative and quantitative research and contemplates the use of multiple methods of investigation. The exploratory qualitative phase was operationalized through semi-structured interviews conducted with managers of the purchases area of two federal universities. The data were treated by applying techniques of content analysis. The quantitative phase consisted in an survey, with the application of a structured questionnaire across the population which comprises 59 federal universities in Brazil. Data collected on 37 valid questionnaires received statistical treatment involving descriptive statistics and correlation calculation. Key findings indicate that: the implementation of sustainable procurement in the federal universities is at an early stage and embryo and that there is not a policy of purchase sustainable clearly defined under most institutions. Actions are specific and do not occur in a strategic and planned level, and are attempts to adapt to the demands normative, motivated by legal changes, especially the establishment of Instruction 01/2010-MPOG/SLTI, considered the main mechanism that prompted the adoption of practice at the federal level and by the decisions and demands of controlling bodies. The most widely used sustainability criteria are primarily those determined and ordered in legislation and the use of criteria is prevalent in contracts involving works and services and engineering, due to higher demand and legal support. The current supply of sustainable products and services, the costs involved, the little information and knowledge, organizational culture and lack of capacity building and training of those involved are among the main barriers identified. A few results and impacts of the implementation of sustainable procurement perceived within universities and is not conducted systematic monitoring of results.